Primary and Chronic HIV Infection Differently Modulates Mucosal Vδ1 and Vδ2 T-Cells Differentiation Profile and Effector Functions - Cimini, Eleonora; Agrati, Chiara; D’Offizi, Gianpiero; Vlassi, Chrysoula; Casetti, Rita; Sacchi, Alessandra; Lionetti, Raffaella; Bordoni, Veronica; Tumino, Nicola; Scognamiglio, Paola; Martini, Federico (PloS one, 2015)
Gut-associated immune system has been identified as a major battlefield during the early phases of HIV infection. γδ T-cells, deeply affected in number and function after HIV infection, are able to act as a first line of defence against invading pathogens by producing antiviral soluble factors and by killing infected cells. Despite the relevant role in mucosal immunity, few data are available on gut-associated γδ T-cells during HIV infection. Aim of this work was to evaluate how primary (P-HIV) and chronic (C-HIV) HIV infection affects differentiation profile and functionality of circulating and gut-associated Vδ1 and Vδ2 T-cells. In particular, circulating and mucosal cells were isolated from respectively whole blood and residual gut samples from HIV-infected subjects with primary and chronic infection and from healthy donors (HD). Differentiation profile and functionality were analyzed by multiparametric flow cytometry. P-HIV and C-HIV were characterized by an increase in the frequency of effector Vδ1-T cells both in circulating and mucosal compartments. Moreover, during P-HIV mucosal Vδ1 T-cells expressed high levels of CD107a, suggesting a good effector cytotoxic capability of these cells in the early phase of infection that was lost in C-HIV. P-HIV induced an increase in circulating effector Vδ2 T-cells in comparison to C-HIV and HD. Notably, P-HIV as well as HD were characterized by the ability of mucosal Vδ2 T-cells to spontaneously produce IFN-γ that was lost in C-HIV. Altogether, our data showed for the first time a functional capability of mucosal Vδ1 and Vδ2 T-cells during P-HIV that was lost in C-HIV, suggesting exhaustion mechanisms induced by persistent stimulation.